2019
DOI: 10.1002/jso.25454
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for integration of palliative care into surgical oncology practice and education

Abstract: High-quality data support multiple clinical benefits of integrating palliative care into routine oncology care. Though these data come largely from the medical oncology literature, data from surgical oncology populations support similar associations between palliative care integration and improved clinical outcomes, all without compromise in survival. This paper will review data supporting palliative care integration into oncology care, with a focus on surgical populations and recommendations for incorporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…However, national cancer registries responsible for all cancer patients should be encouraged to collect relevant data for treatment aspects beyond curative intention. Modern palliative care provides a broad spectrum of options to improve and maintain quality of life or optimise end-of-life care [28]. Hopefully, the increased focus on patient-reported outcomes (PROM) will enable cancer registries to provide data to evaluate treatments from the patient perspective [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, national cancer registries responsible for all cancer patients should be encouraged to collect relevant data for treatment aspects beyond curative intention. Modern palliative care provides a broad spectrum of options to improve and maintain quality of life or optimise end-of-life care [28]. Hopefully, the increased focus on patient-reported outcomes (PROM) will enable cancer registries to provide data to evaluate treatments from the patient perspective [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a collaborative approach and optimization of underlying conditions, studies have also shown that early palliative care consultation can lead to improvements in symptom management, quality of life, and spiritual satisfaction, and should be considered in all patients with advanced malignancy. 41,42 The lack of preoperative guidelines for patients with cancer underscores the need for more research focusing on this high-risk population. Treatment strategies should focus on timely diagnostic evaluation, early surgeon consultation, the inclusion of a comprehensive treatment team, and individualized treatment decisions based on a multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is true that most part of the literature that shows evidence on the integration of palliative care to cancer treatment originates from studies in the field of clinical oncology, there is also evidence on the benefits of palliative care in surgical oncology units, including an improvement in patient-reported outcomes and a decrease in the use of resources, without survival being compromised 10 . For example, in a study that evaluated 34,000 patients who died in a surgical unit for several types of cancer over a 10-year period, those patients who had access to palliative care were shown to have a significant decrease in end-of-life aggressive care such as chemotherapy, emergency room visits, hospitalizations, and intensive care unit admissions within the past 30 days before death, and in-hospital death 11 .…”
Section: Gaceta Mexicana De Oncologíamentioning
confidence: 99%